Quality Culture in Teacher Education - Sharma, K.K.; Sobit, Saroj (JOURNAL OF INDIAN EDUCATION, 2010)
The management and sustenance of quality in Higher Education is a great challenge for the policy planners and managers in the changing scenario. Management of the functioning of an educational institution that is utilization of resources- men, material, machine, money, time and space, innovative practices and intuitive future plan lead to the enhancement of quality. The National Assessment and Accreditation Council (NAAC) came into existence as deliberate government intervention to help institutions to integrate quality initiatives for attaining national goals of equity, excellence and efficiency. The central focus of this article is to discuss about the various healthy or innovative practices for the enhancement of quality environment suggested by this Council. It also put forth some suggestions to improve the current scenario of Indian Educational Institutions.